Large Fecal Reservoir of Escherichia coli Sequence Type 131-H30 Subclone Strains That Are Shared Within Households and Resemble Clinical ST131-H30 Isolates - Mohamed, Muhanad; Clabots, Connie; Porter, Stephen B; Bender, Tricia; Thuras, Paul; Johnson, James R (The Journal of infectious diseases, 2020)
Abstract Background Emerging antimicrobial-resistant Escherichia coli represent mainly the nested (fluoroquinolone-resistant [FQR]) H30R and H30Rx subclones within sequence type 131 (ST131). Intestinal colonization and within-household transmission may underlie H30R’s emergence. Methods We screened fecal samples from 741 volunteers (383 veterans, 358 household members, including pets) for ST131 and FQR E. coli (FQREC) and used molecular profiling to resolve unique strains. Selected strains underwent PCR-based detection of phylogroups, sequence types (STs), H30, H30Rx, and 53 virulence genes (VGs). Within-household strain sharing was compared with household, host, and bacterial characteristics. Fecal isolates were compared with clinical isolates. Results Colonization prevalence was 5.1% for H30R, 8% for ST131 (67% FQREC), and 10% for FQREC (52% ST131). ST131 isolates exhibited more VGs than non-ST131 isolates. Strain sharing (27% of multisubject households, 18% of corresponding subjects) was associated with the elderly, FQREC, H30R, H30Rx, ST73, and specific VGs. Fecal ST131 and FQREC isolates resembled contemporaneous and historical clinical isolates according to all studied traits. Conclusions Veterans and their human household members commonly carry and extensively share FQREC, predominantly H30R, thereby likely facilitating the ST131 pandemic. Strain sharing corresponds with multiple bacterial characteristics, including FQ resistance and specific VGs, which may promote intestinal colonization and/or host-to-host transmission. Uninfected veterans and their household members commonly carried and shared fluoroquinolone-resistant gut E. coli, predominantly ST131-H30R, likely facilitating the ST131 pandemic. Strain sharing corresponded with fluoroquinolone resistance and specific “virulence genes,” which may also promote intestinal colonization and/or host-to-host transmission.